Effect of variations in Composition and Sintering Temprature on Mechanical Properties Ceramic Membrane with Bentonite, Sinabung Volcanic Ash and Carbon Active. Issue 1 (June 2021) - Hasanah, Moraida; Sembiring, Timbangen; Sebayang, Kerista; Humaidi, Syahrul; Rahmadsyah,; Fynnisa, Z
Abstract: All articles must contain an abstract. The abstract text should be formatted using 10 point Times or Times New Roman and indented 25 mm from the left margin. Leave 10 mm space after the abstract before you begin the main text of your article, starting on the same page as the abstract. The abstract should give readers concise information about the content of the article and indicate the main results obtained and conclusions drawn. The abstract is not part of the text and should be complete in itself; no table numbers, figure numbers, references or displayed mathematical expressions should be included. It should be suitable for direct inclusion in abstracting services and should not normally exceed 200 words in a single paragraph. Since contemporary information-retrieval systems rely heavily on the content of titles and abstracts to identify relevant articles in literature searches, great care should be taken in constructing both.